Determinants of firms innovation in France: an empirical approach - Quintero Torres , Angela Jiseth
The study aims to establish the main determinants of business innovation in France with an explanatory scope. Econometric techniques were used to respond to the probability of innovation: logit and probit. The estimate used the World Bank database (2023) obtained from surveys of French companies in 2021 from the Enterprise Surveys. One of the main findings was the importance of investment in research and development for both process and product innovation, which highlights the relevance of support for the generation of scientific knowledge for the development of technological advances that promote innovation in French companies. In addition, the unexpected negative impact that experience has on the probability of innovating in companies. These results demonstrate the importance of supporting determinants that generate business innovation and correcting variables with negative impacts, suggesting that, if France wants to improve its international position by improving its economy, companies and their growth are a decisive factor. This is why factors related to business growth such as innovation should be supported by both private and national state entities.